PELATIHAN TECHNOPRENEURSHIP UNTUK PENGELOLAAN BANK SAMPAH, DESA MADUREJO, PRAMBANAN, SLEMAN - Agus Hindarto Wibowo; Ramja Hidayat; Abdulah Aris Aminudin (LPPM IST AKPRIND Yogyakarta, 2020)
Waste always becomes problem faced by people in various regions in Indonesia, including Yogyakart. So, a comprehensive solution to the waste problem is needed. One alternative solution that can be done is to provide education to the community in waste management using current technology, namely internet-based technology. The Madurejo Village Youth Organization, Prambanan, Sleman has the intention to make a new breakthrough in processing waste with internet-based technology, that it can have a positive impact on the organization and environment of the Village. For this reason, it is necessary to conduct a socialization of waste management with internet-based technology at the Madurejo Village Youth Organization. The purpose of this socialization is that Madurejo Village Youth can operate an internet-based waste management system: an application in waste processing to the marketing process.The results obtained after the socialization was conducted, the Madurejo Village Youth were very enthusiastic in participating in the socialization, and would implement the application in carrying out waste management, so it would provide financial benefits for the Youth Organization and generally for Madurejo Village